Financial Education: A study on its importance in personal management (Research, Society and Development, 2023)
Financial education is a topic of utmost importance in a world in which personal finances play a key role in people's lives. This field of study seeks to promote the knowledge and skills necessary for efficient money management, informed financial decision-making, and the achievement of financial stability. Thus, the objectives of this study are to emphasize the importance of financial education in personal management, analyze the situation of Brazilians regarding financial education, understand the impacts of poor financial management from the socioeconomic perspective of individuals, and present recommendations mentioned in the literature to mitigate the negative effects of poor financial management. The methodology employed, on the other hand, adopts a descriptive approach, using as main procedure the application of a questionnaire conducted on Google Forms, having been disseminated through the WhatsApp social network. The results of this study revealed that of the 59 participants, the vast majority belonged to socioeconomic classes C and D. Moreover, it was found that, despite having some level of knowledge regarding financial education, many of these individuals faced difficulties related to financial default. Among the main factors pointed out was the use of credit cards, followed by financial contingencies, lack of financial control, job loss, and loans. The results obtained in this study were consistent with research previously conducted by national institutions, showing a correspondence between the data and information available in the literature and those found in this research.